Retraction: Self-assembled chalcopyrite ternary semiconductor CuBSe2 nanocrystals: solvothermal synthesis and characterisation. Issue 16 (7th April 2022) - Chen, Lin-Jer; Liao, Jiunn-Der; Chuang, Yu-Ju
Abstract : Retraction of 'Self-assembled chalcopyrite ternary semiconductor CuBSe2 nanocrystals: solvothermal synthesis and characterisation' by Lin-Jer Chen et al., CrystEngComm, 2011, 13, 2909–2914; DOI: ; 10.1039/C0CE00818D .